Textverstehen im fremdsprachenunterricht - Гресь, А. А.; Gres, A. A. (My University, 2010)
The peculiarities of the apprehension the foreign texts have been analyzed. The main reasons and difficulties of the understanding the authentic foreign texts while reading and listening have been found up. The main approaches strategies that will help to understand the foreign text have been described
Gres, A. A. Textverstehen im fremdsprachenunterricht / А. А. Gres // Гуманіт. вісн. НУК. – Миколаїв : НУК, 2010. – Вип. 3. – С. 114–116.
Keywords: difficulties of understanding; unknown; authentic texts; work is with text; forming of hypothesis; strategies of understanding